Age and sex differences in the association between APOE genotype and Alzheimer’s disease in a Taiwan Chinese population - Huang, Ling-Chun; Lee, Mei-Yueh; Chien, Ching-Fang; Chang, Yang-Pei; Li, Kuan-Ying; Yang, Yuan-Han (Frontiers in Aging Neuroscience, 2023)
The Apolipoprotein E (APOE) epsilon (ɛ) 4 allele is a well-established risk factor for late-onset Alzheimer's disease (AD). Reports on white ancestry populations have showed that age, sex, and ethnicity have different effects on the association between APOE genotype and AD. However, studies on Asian populations such as Taiwan Chinese populations are limited. This study aimed to evaluate the association between APOE genotype and AD in a Taiwan Chinese population, and to explore if the association varies by age and sex.Methods: We conducted a case-control study in 725 patients with AD and 1,067 age-and sexmatched controls without dementia from a Taiwan Chinese population. Logistic regression models were used to test the association between AD and APOE genotypes. Secondary analyses considered age (<75 or ≥75 years old), and sex stratified models.Results: The risk of AD was significantly increased for people with at least one copy of APOE ɛ4 (OR=2.52, 95% CI=2.01-3.17, p< 0.001) and in a dose-dependent manner. Our results did not show an statistically significance different in AD risk when women and men carrying APOEɛ4 were compared. Despite not reaching statistical significance, the risk of APOE ɛ4 for AD was higher among younger participants (OR=3.21, 95% CI=2.26-4.56, p< 0.001) compared to older ones (OR=2.13, 95% CI=1.53-2.97, p< 0.001). When considering both sex and age, the risk of AD was higher among older men carrying APOE ɛ4 (OR = 2.64, 95% CI = 1.51-4.60 in men; OR = 1.90, 95% CI = 1.26-2.86 in women), while women carrying APOE ɛ4 appeared to have an increased risk at a younger age (OR = 3.29, 95% CI = 2.20-4.93 in women; OR = 2.91, 95% CI = 1.40-6.05 in men).Discussion: The APOE ɛ4 allele represents a major risk factor for AD in the Taiwanese population. The effect of APOE ɛ4 allele on AD risk appeared to be stronger among men aged 75 years or more and among younger women.